A STUDY OF HISTORICAL ASPECTS OF THE CONFESSIONAL POETRY IN ROBERT LOWELL’S LIFE STUDIES - Rania Saber Ahmed Abdel Rahim (EJI (English Journal of Indragiri) : Studies in Education, Literature, and Linguistics, 2021)
Robert Lowell, the iconic American Poet, moves with his Confessional poetry, notably the poetic volume Life Studies (1959) from the “raw” to the “cooked”. Confessional poetry is similar to the art of confession. Moreover, the historical poetic pieces implied more than the mere gathering of fact and figures. For Lowell history manifested itself in the affairs of men and it is a persistent and violent force. Such a view is not entirely optimistic, springing directly from this view is Lowell's deep sense of loss, failure, alienation, helplessness and a feeling of entrapment in a world not of his making. In the light of the New Historicism approach, Lowell managed to perceive the literary text as a communal product which sought to reconnect itself to its cultural context. He did not think only of the past but took history forward into the present with all its discourse on culture, and its components, religious and political tradition of the place itself. Hence, in order to study the confessional poetry, historical aspects and the consequences of their psychoanalytic literary approach objectively play a significant role.